Animal Breeding for Poverty Alleviation: Harnessing Science for Greater Impact: Foreword to the special issue of Livestock Science - Hunter, B.; Bindon, B.; Dargie, J.D.; Piper, L.; Seré Rabé, Carlos (Elsevier, 2011)
This special issue of Livestock Science is dedicated to the work and life of John Vercoe and particularly to his tireless pursuit of bringing – directly through his own endeavours and indirectly through the encouragement and inspiration he gave to so many others – the best in Australian and international research and applications of animal breeding for improving livelihoods throughout the world. The papers represent a small selection of the many contributions made by specialists attending an International Conference entitled “Animal Breeding for Poverty Alleviation: Harnessing Science for Greater Impact” which was convened by the International Livestock Research Institute (ILRI) in memory of John and which was marked by the opening of the John Vercoe Conference Hall by John's wife Jan, accompanied by their children Megan, Tim and Philip.